2019
DOI: 10.1002/er.4783
|View full text |Cite
|
Sign up to set email alerts
|

PEMFC purging at low operating temperatures: An experimental approach

Abstract: SUMMARY In this paper, the effect of operating temperature on optimal purge interval for maximum energy efficiency in a proton exchange membrane fuel cell (PEMFC) with dead‐ended anode (DEA) was experimentally investigated. The study was conducted with a focus on challenges associated with operation at temperatures lower than the recommended designed temperature. With DEA, gradual voltage drop happens due to the accumulation of water and impurities such as nitrogen. Hence, periodic purging of the anode side is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
(184 reference statements)
0
16
0
Order By: Relevance
“…When the current is 25 A, the voltage of Cell 13, Cell 15, and Cell 17 gradually decreases, as shown in Figure A. Gradual voltage drop happens due to the accumulation of water . These phenomena proved the occurrence of the anode flooding.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…When the current is 25 A, the voltage of Cell 13, Cell 15, and Cell 17 gradually decreases, as shown in Figure A. Gradual voltage drop happens due to the accumulation of water . These phenomena proved the occurrence of the anode flooding.…”
Section: Resultsmentioning
confidence: 91%
“…Gradual voltage drop happens due to the accumulation of water. 38 These phenomena proved the occurrence of the anode flooding. Liquid water blocked the gas passage in the anode GDL, so that the reaction gas entering the catalytic layer was greatly reduced.…”
Section: Characteristic Of the Cell Voltagementioning
confidence: 91%
“…The effects of gas purging on water management have been investigated through both experiments and numerical simulations. 25,26 Zhang et al 27 systematically studied the effects of the purging parameters on the performance of a high-temperature proton exchange membrane fuel cell (HT-PEMFC). The results showed that the anode purging process could improve both the performance and fuel utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The anode fuel supply management impacts directly the PEMFC operation efficiency and durability. In general, three anode modes including flow‐through mode, dead‐end mode, and recirculation mode, are used to supply hydrogen in a PEMFC system 1,2 . Hydrogen recirculation mode can improve the efficiency and durability of the fuel cell with the advantage of humidifying the dry supplied hydrogen, discharging water timely, and distributing accumulated inert gases 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, three anode modes including flowthrough mode, dead-end mode, and recirculation mode, are used to supply hydrogen in a PEMFC system. 1,2 Hydrogen recirculation mode can improve the efficiency and durability of the fuel cell with the advantage of humidifying the dry supplied hydrogen, discharging water timely, and distributing accumulated inert gases. 3 Hence an effective hydrogen recirculation device is of great importance to enhance the performance of PEMFC systems.…”
Section: Introductionmentioning
confidence: 99%